NEMO v4.2 eORCA1 data with RIS, FRIS and LCIS explicit - Katherine Hutchinson; Julie Deshayes; Christian Éthé; Clement Rousset; Casimir de Lavergne; Martin Vancoppenolle; Nicolas C. Jourdain; Pierre Mathiot (Zenodo, 2023)
PROJECT OPEN https://www.katofthesea.com/project-open OBJECTIVES As a first step towards better representing AABW source waters in NEMO global ocean 1° (eORCA1), we explicitly simulate circulation beneath Filchner-Ronne (FRIS), Larsen C (LCIS), and Ross (RIS) ice shelves. These ice shelves were chosen due to their role in the formation and setting of properties of the parent waters of AABW. METHODOLOGY NEMO version 4.2 Beta Forced with 2 cycles of CORE forcing for a reference “Closed” cavity run and an “Open” run with FRIS, LCIS and RIS represented. Inform initial conditions using an idealized regional configuration of each ice shelf. PROVIDED HERE: NAMELISTS: - NEMO reference namelist (namelist_ref; alsoavailable with NEMO code), OPEN configuration (namelist_core_ia_cfg) namelist and sea ice namelists (namelist_ice_ref and namelist_ice_cfg). Unless stated otherwise in the “cfg” namelist, the simulation uses the namelist choices provided in the “ref” namelist. The namelist_core_ia_cfg is a namelist specific to a global ocean configuration (ORCA2, ORCA1, ORCA025 etc) forced by interannual core winds. For more information on all the namelist parameters included in these namelists, please refer to the NEMO reference manual available on Zenodo (10.5281/zenodo.6334656). DOMAIN FILES AND INITIAL CONDITIONS: - Initial conditions where data inside the cavity is informed using an idealized regional configuration with World Ocean Atlas (WOA; https://www.nodc.noaa.gov/OC5/woa18/woa18data.html )restoring at the boundaries. The data in the cavities is merged with WOA with a smoothing spline applied along the ice shelf front. - A domain file containing bathymetry and ice shelf draft with FRIS, LCIS and RIS open along with accompanying mesh mask file. - The adapted eddy viscosity files where viscosity varies south of 65 degrees South according to grid cell size. - A freshwater flux file where the melt rate from all cavities except FRIS, LCIS and RIS is prescribed. Inside the "Open" cavities, the melt paramaterization is turned ...